Associations of momentary food availability and appetitive drive with adolescents' food intake and dysregulated eating in a community sample of adolescents: The moderating role of trait hedonic hunger - Yue Luo; Jeremy C. Morales; Kathryn E. Smith; Tyler B. Mason (Applied Psychology: Health and Well-Being, 2026)
Abstract Using ecological momentary assessment (EMA), we tested whether momentary palatable food availability and appetitive drive predict adolescents' palatable food/drink intake and dysregulated eating and whether trait hedonic hunger moderates these momentary links. Adolescents aged 13–17 ( N = 74) completed a 10‐day smartphone EMA protocol with three to seven semi‐randomly delivered surveys daily and event reports of eating episodes. Outcomes included intake of sweet foods, salty/fried foods, and sugar‐sweetened beverages (SSBs), plus momentary loss of control eating (LOCE) and overeating symptoms. Generalized linear mixed models separated within‐person (momentary elevations) from between‐person (average differences) effects and tested trait hedonic hunger (Power of Food Scale) as a moderator. Higher trait hedonic hunger was associated with greater odds of intake of sweet foods and SSBs and with greater LOCE and overeating. Within‐person increases in food availability prospectively predicted higher odds of sweet food intake at the subsequent eating episode, and between‐person food availability was associated with higher odds of salty/fried foods intake. Appetitive drive was inversely associated with sweet food intake. Trait hedonic hunger strengthened the positive association between appetitive drive and subsequent salty/fried food intake and LOCE. Findings emphasize the need to consider both momentary contexts and trait‐level factors when designing strategies to support healthy eating among adolescents.